Clinical Characteristics and Risk Factors for Blood Culture-Positive Klebsiella pneumoniae Liver Abscess: A Retrospective Study - Zhang HF; Chen JW; Li SS; Wu SW; Li S; Liu CY; Cai C; Lu MQ (International Medical Case Reports Journal, 2025)
Hui-Fang Zhang,* Jia-Wen Chen,* Shan-Shan Li, Shi-Wen Wu, Shu Li, Chen-Yi Liu, Chao Cai, Ming-Qin Lu Department of Infectious Diseases, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ming-Qin Lu; Chao Cai, Department of Infectious Diseases, The First Affiliated Hospital of Wenzhou Medical University, No. 1 Nanbaixiang Street, Ouhai District, Wenzhou, Zhejiang, 325000, People’s Republic of China, Email lmq0906@163.com; caichao@wmu.edu.cnBackground: Positive blood cultures for Klebsiella pneumoniae liver abscess (KPLA) are associated with an increased risk of extrahepatic organ infections and severe complications such as septicemia and septic shock, leading to higher mortality rates. This study aimed to investigate the clinical characteristics of patients with blood culture-positive KPLA and identify potential predictive indicators.Methods: We performed a retrospective analysis of clinical data from 263 KPLA patients diagnosed at our hospital between January 2019 and December 2023. The objective was to compare clinical characteristics between patients with positive and negative blood cultures and explore factors influencing blood culture positivity. Patients were divided into a blood culture-positive group (study group) and a blood culture-negative group (control group). We compared baseline characteristics, laboratory parameters, ultrasound findings, and complications. Logistic regression identified risk factors, and receiver operating characteristic (ROC) curves assessed the predictive value of inflammatory markers.Results: The study group exhibited higher ICU admission rates, longer hospital stays, and elevated qSOFA scores (≥ 2, 15.1 vs 2.6, P=0.003) along with a greater prevalence of diabetes and biliary diseases. Key laboratory values, including glucose, creatinine, procalcitonin (PCT), and C-reactive protein (CRP), were significantly higher, while albumin and platelet levels were lower (P < 0.05). Complications such as pleural effusion (35.1 vs 12.8, P< 0.001), ascites (15.1 vs 2.6, P=0.003), pulmonary infections (27.6 vs 7.7, P< 0.001), and extrahepatic abscesses (15.7 vs 5.1, P=0.018) were notably more common. Diabetes was identified as an independent risk factor for blood culture-positive KPLA. Among inflammatory markers, PCT showed the highest predictive value for blood culture positivity (AUC=0.683; cutoff=4.97 ng/mL; sensitivity=70.3%; specificity=62.8%).Conclusion: Patients with underlying diabetes mellitus are more prone to developing blood culture-positive KPLA. PCT demonstrates better predictive performance for blood culture-positive KPLA, and patients with PCT levels ≥ 4.97 ng/mL have a higher likelihood of positive blood culture results.Keywords: blood culture positivity, Klebsiella pneumoniae, hepatic abscess, clinical features, risk factors